If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying R = (12 + -0.5x)(36 + 2x) Multiply (12 + -0.5x) * (36 + 2x) R = (12(36 + 2x) + -0.5x * (36 + 2x)) R = ((36 * 12 + 2x * 12) + -0.5x * (36 + 2x)) R = ((432 + 24x) + -0.5x * (36 + 2x)) R = (432 + 24x + (36 * -0.5x + 2x * -0.5x)) R = (432 + 24x + (-18x + -1x2)) Combine like terms: 24x + -18x = 6x R = (432 + 6x + -1x2) Solving R = 432 + 6x + -1x2 Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Simplifying R = 432 + 6x + -1x2
| 332-312= | | 6x-8+2(5x+3)=-2(x+3) | | 1/2x=(-3) | | (4n-2)/7=3 | | Y=450-10x | | c-1.23=0.18 | | 25X+Y-400=0 | | a(2)=3/2(2)-1 | | 2+8x= | | 4x=(9x-1) | | 3m+9m+10-5=20 | | a(1)=3/2(1)-1 | | f(n)=3f(n-1)-3 | | 16X+9Y+160X-18Y+265=0 | | 8x+18=8x+18 | | -7+2h=-h+10+10 | | 208/4=832/x | | -31/2=-1/1g | | x+15(2)=3x+20 | | an=3/2(1)-1 | | 10b+4=-8+8b | | 12=a-6.4 | | 3(2x-1)-4x-2x-6=-9 | | 676X+567+4056X+1152Y-382716=0 | | 3(3w+7)=68 | | 5(-3.25)+5(-6.75)= | | (5/9)^3×(18/25)^2 | | -2(-10+x)=26 | | 49.50/16.50 | | 3/35.46=6/x | | 10w+3=83 | | -(2x+4)+8x+(-6)= |